Association Between Lactates, Blood Glucose, and Systemic Oxygen Delivery in Children After Cardiopulmonary Bypass - Klee, Philippe; Rimensberger, Peter C.; Karam, Oliver (Frontiers in Pediatrics, 2020)
Objective: Lactate is often used as a surrogate marker of inappropriate oxygen delivery. It has been shown that hyperlactatemia is associated with worse clinical outcome in children after cardiac surgery. The purpose of this study is to evaluate the association of hyperlactatemia, low systemic oxygen delivery, and hyperglycemia, in children admitted to the pediatric critical care unit after cardiopulmonary bypass. Design: Secondary analysis of an observational cohort study. Setting: Tertiary pediatric critical care unit (PICU). Patients: Ninety-three patients, aged six months to sixteen years, undergoing cardiac surgery with cardiopulmonary bypass. Interventions: None. Measurements and Main Results: Metabolic tests (blood glucose, lactate, lactate/pyruvate ratio, and ketones) and oxygen extraction (SaO2-SvO2) were performed before anesthesia, at the end of cardiopulmonary bypass, at PICU admission, and at 4 and 12 hours after PICU admission. Four hours after PICU admission, 62% of the patients had hyperlactatemia (> 2 mmol/L), of whom 55% had normal oxygen extraction (SaO2-SvO2 < 30%). There was no correlation between lactate and oxygen extraction (R= -0.09, p=0.41) but there was a moderate correlation between lactate and blood glucose (R=0.55, p<0.001). Using a logistic regression model, hyperlactatemia at 4 hours after PICU admission was independently associated with hyperglycemia (p=0.007) and lactate/pyruvate ratio (p=0.007) at the same timepoint, as well as with lactate at PICU admission (p=0.002), but not with weight (p=0.45), severity of the cardiac lesion (p=0.85), duration of bypass (p=0.16), or oxygen extraction, as evaluated by SaO2-SvO2 (p=0.54). At 12 hours after PICU admission, there was a very week correlation between lactate and blood glucose (R=0.27, p=0.007), but none between lactate and oxygen extraction (R= 0.13, p=0.20). Conclusion: In children after cardiopulmonary bypass, lactates are not correlated with higher oxygen extraction, but are correlated with hyperglycemia, at both 4 and 12 hours after PICU admission. Future research is warranted to better define this relationship.